ANALISIS ELECTRONIC PARKING UNTUK MENDUKUNG PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN INDRAGIRI HILIR - Rianto, Bayu; Syah, Muhammad Rayhan; Karudin, Arwizet; Jalil, Muhammad; Chrismondari, Chrismondari (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2023)
There are several sources of Regional Own-Source Revenue (PAD) in accordance with Law number 1 of 2022, one of which is parking fees that falls under local fees. To optimize and enhance the Regional Own-Source Revenue (PAD), professional and transparent management of parking fees is necessary. This study aims to determine the design of an information system, its effectiveness, and the advantages and disadvantages of using an electronic parking system for paying parking fees in Indragiri Hilir Regency. This research falls within the realm of qualitative research. The data sources used in this study include primary and secondary data. Data was collected through interviews, observations, documentation, and literature review. Data analysis techniques employed encompass data collection, data reduction, data presentation, verification, and conclusions. The management of parking fees still encounters several obstacles, including a lack of field supervision, exploitation by irresponsible individuals taking advantage of negligence for personal gain, and incomplete allocation of parking revenue to local governments. One solution to address leakages in the management of parking fee funds is the implementation of electronic parking, enabling effective monitoring of all parking-related aspects, thereby contributing to an increase in Regional Own-Source Revenue from the local fee sector, specifically parking fees.